The structural modification of natural products for novel drug discovery - Yao, Hong; Liu, Junkai; Xu, Shengtao; Zhu, Zheying; Xu, Jinyi (Taylor & Francis, 2016)
Introduction: Throughout history, natural products (NPs) have provided a rich source of compounds that have wide applications in the fields of medicine, health sciences, pharmacy and biology. Although naturally active substances are good lead compounds for the discovery of new drugs, most of them suffer from various deficiencies or shortcomings, such as complex structures, poor stability and solubility. Therefore, structural modification of NPs is needed to develop novel compounds with specific properties.